EFFECTS OF OCCLUSAL CORRECTION THERAPY AND NON-SURGICAL PERIODONTAL THERAPY IN PATIENTS WITH CHRONIC PERIODONTITIS AND BRUXISM - Cosmin Gabriel Popa; Ioana Martu; Ruxandra Stan; Elena Odette Luca; George Alexandru Maftei; Oana Bejan; Maria Alexandra Martu (Romanian Dental Association for Education, 2024)
This study aimed to evaluate the degree of periodontal involvement in subjects with and without bruxism, with generalized chronic periodontitis of varying severity grades, and to assess the effects of occlusal correction therapy in association with non-surgical periodontal therapy on periodontal status. The following periodontal parameters were analyzed: probing depth (PD), clinical attachment level (CAL), Papilar bleeding index (PBI) and Plaque Index (PI), and X-rays, at the initial (pre-therapeutic) moment and at 3 months after therapy completion. The present study demonstrated that bruxism generates significant clinical changes in a periodontopathic environment. High values of periodontal attachment loss, recessions, missing teeth, tooth mobility, and furcation lesions translate into major losses of periodontal tissue in patients with periodontal disease and bruxism. Periodontal therapy, combined with occlusal correction and bruxism therapy, resulted in statistically significant improvements in periodontal parameters. Thus, occlusal trauma therapy in patients with bruxism becomes an absolute necessity in periodontal therapy.